2020
DOI: 10.3390/insects11050286
|View full text |Cite
|
Sign up to set email alerts
|

First Report Using a Native Lacewing Species to Control Tuta absoluta: From Laboratory Trials to Field Assessment

Abstract: The South American tomato pinworm, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), a destructive pest on tomato, has invaded most Afro-Eurasian countries. Recently invaded by the pest, most tomato crops in greenhouses and open fields in Tajikistan are currently suffering major damage. While failure in management using chemical insecticide has been frequently observed, alternative options such as biological control is urgently needed. In this study, we evaluated the effectiveness of the common green lacewin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Despite some inconsistent laboratory vs. field data for SWD predation [ 13 , 14 , 16 , 23 ], other studies have shown that Chrysopids are promising predators to be used in the control of other insect pests: Chrysoperla spp. larvae might be used to control Tuta absoluta (Meyrick) (tomato pinworm) [ 39 ], Frankliniella occidentalis Pergande (western flower thrips) [ 40 ], Melanaphis sacchari (Zehntner) (sugarcane aphid) [ 41 ] or Glycaspis brimblecombei Moore (eucalyptus aphid) [ 42 ]. However, the role of chrysopids remains unclear, as the collected individuals were adults, and not all adults of the family Chrysopidae are predators.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some inconsistent laboratory vs. field data for SWD predation [ 13 , 14 , 16 , 23 ], other studies have shown that Chrysopids are promising predators to be used in the control of other insect pests: Chrysoperla spp. larvae might be used to control Tuta absoluta (Meyrick) (tomato pinworm) [ 39 ], Frankliniella occidentalis Pergande (western flower thrips) [ 40 ], Melanaphis sacchari (Zehntner) (sugarcane aphid) [ 41 ] or Glycaspis brimblecombei Moore (eucalyptus aphid) [ 42 ]. However, the role of chrysopids remains unclear, as the collected individuals were adults, and not all adults of the family Chrysopidae are predators.…”
Section: Discussionmentioning
confidence: 99%
“…Natural predators of T. absoluta are Macrolophus pygmaeus Rambur and Nesidiocoris tenuis Reuter [ 67 ]. Other effective natural enemies are Chrysoperla carnea (Stephens) and Dicyphus errans (Wolff), that could be successfully integrated in pest management strategy if their habitat conservation is followed [ 68 , 69 ]. Trichogramma pretiosum (Riley) and T. brassicae Bezdenko are popular egg parasitoids of TLM [ 70 ].…”
Section: Management Strategies Of T Absolutamentioning
confidence: 99%
“…The eggs of E. kuehniella are commonly utilized as factitious prey items in the mass rearing programs of natural enemies [17], which is why we used this prey for comparison purposes. Leucoptera coffeella is considered one of the most economically significant pest species of coffee in Brazil [18]; the exposed nature of the pupal stage renders it readily accessible for C. externa consumption, unlike eggs and larvae within the mines [15]. The eggs of D. saccharalis, a key sugarcane pest in South America, can also serve as natural prey for green lacewing larvae [19].…”
Section: Introductionmentioning
confidence: 99%